2015
DOI: 10.1017/s0954579414001357
|View full text |Cite
|
Sign up to set email alerts
|

Brain-derived neurotrophic factor (BDNF) Val66Met polymorphism influences the association of the methylome with maternal anxiety and neonatal brain volumes

Abstract: Early life environments interact with genotype to determine stable phenotypic outcomes. Here we examined the influence of a variant in the brain-derived neurotropic factor (BDNF) gene (Val66Met), which underlies synaptic plasticity throughout the central nervous system, on the degree to which antenatal maternal anxiety associated with neonatal DNA methylation. We also examined the association between neonatal DNA methylation and brain substructure volume, as a function of BDNF genotype. Infant, but not materna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 116 publications
2
74
0
Order By: Relevance
“…Anxiety appears to be an important factor influencing BDNF expression the amygdala, as maternal anxiety impacts DNA methylation of Met/Met genotype of the BDNF Val66Met gene variant in infants and effects amygdalar volume (Chen et al, 2015). Alcohol treatment during early postnatal rat development enhances BDNF and GDNF expression in the central extended amygdala (Balaszczuk et al, 2013), and ETOH withdrawal in adult rats leads to decreased BDNF gene expression and dendritic spine density in the CeA along with increased anxious behavior (You et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Anxiety appears to be an important factor influencing BDNF expression the amygdala, as maternal anxiety impacts DNA methylation of Met/Met genotype of the BDNF Val66Met gene variant in infants and effects amygdalar volume (Chen et al, 2015). Alcohol treatment during early postnatal rat development enhances BDNF and GDNF expression in the central extended amygdala (Balaszczuk et al, 2013), and ETOH withdrawal in adult rats leads to decreased BDNF gene expression and dendritic spine density in the CeA along with increased anxious behavior (You et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Here, maternal anxiety decreased cortical thickness in neonates with two copies of the Met COMT allele but increased cortical thickness in neonates with two copies of the Val allele. BDNF genotype may also regulate the sensitivity of the methylome [G] to maternal anxiety, with differential effects on amygdala and hippocampal volume 160 . Finally, it has also recently been reported that the common variant rs17203281 in DLG4 (also known as PSD95 , which encodes postsynaptic density protein 95) is associated with significant differences white-matter microstructure (as indexed by FA) in preterm infants.…”
Section: Influences Of Genes and Environmentmentioning
confidence: 99%
“…The former view that DNA methylation within the promoter region leads to gene silencing, has also been challenged recently, as more and more reports also show a positive relation between methylation and expression (Ehrlich and Lacey, 2013). Lately, the interaction between genotypes and DNA methylation has also found increased attendance, as some genotypes can affect DNA methylation throughout the whole genome (Chen et al, 2015).…”
Section: Introductionmentioning
confidence: 99%